Synthesis of the furo[2,3-b]chromene ring system of hyperaspindols A and B - Paterson, Danielle L.; Barker, David (Beilstein Journal of Organic Chemistry, 2015)
The synthesis of the unique furo[2,3-b]chromene ring system found in hyperaspidinols A and B, acylphloroglucinols from Hypericum chinense has been achieved in twelve steps. By comparison of the NMR spectra of the synthesized compounds with those of the natural products, a relative stereochemistry is suggested, especially that of the ketal carbon.
Keywords: acylphloroglucinols; bicyclisation; furo[2,3-b]chromene; fused ketal